Financial Ratio, Distress, and Performance in Indonesian Transportation Companies - Candy, Candy; Sisca, Veni (Almana : Jurnal Manajemen dan Bisnis, 2023)
A company with a large amount of debt certainly increases the possibility of financial distress and affects its financial performance. Transportation and logistics are the top three industries with the highest average debt-to-assets ratio. Therefore, this study aims to determine whether financial ratios affect financial distress and whether financial distress mediates the influence between these two variables through a panel analysis method, with a sample of 21 IDX-listed companies from 2017-2021. This analysis shows that CR and DAR significantly negatively impact financial distress, while DER, OCF, and TATO do not considerably affect financial distress. In addition, financial distress does not significantly affect financial performance, nor does not mediate the effect of financial ratios on financial performance.